2008
DOI: 10.1063/1.2952556
|View full text |Cite
|
Sign up to set email alerts
|

Coercivity generation of surface Nd2Fe14B grains and mechanism of fcc-phase formation at the Nd/Nd2Fe14B interface in Nd-sputtered Nd–Fe–B sintered magnets

Abstract: The coercivity of surface grains of a Nd-Fe-B sintered magnet can be measured unequivocally if the magnet is a thin slab with the orientation of its c-axis parallel to the largest surface. Due to the loss of part of the neodymium-rich grain boundary phase, the surface Nd 2 Fe 14 B grains have low coercivity after machining. When a Nd layer is sputter deposited on the surface and annealed in the temperature range from 500 to 675°C, the surface coercivity recovers to its full value, which is identical to the coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 13 publications
(12 reference statements)
2
25
0
Order By: Relevance
“…The addition of Cu promotes this microstructural evolution of Nd-rich GBP and forms a thin Cu-enriched layer along the Nd-rich GBP//Nd 2 Fe 14 B interface because of the eutectic decomposition of Nd-Cu at 520°C [6,7]. Crystal structure changes of the Nd-rich phase, induced by PSA, have been also reported using a simple model system [8][9][10]. The most stable hNd 2 O 3 phase is formed away from the Nd 2 Fe 14 B//Nd-rich phase interface, but the meta-stable fcc-NdO 2 phase (a = 0.54 nm), which is related to the C-Nd 2 O 3 (Ia 3, a = 1.108 nm) phase, is formed at the interface in the sample whose coercivity was recovered during 550°C annealing [8][9][10].…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…The addition of Cu promotes this microstructural evolution of Nd-rich GBP and forms a thin Cu-enriched layer along the Nd-rich GBP//Nd 2 Fe 14 B interface because of the eutectic decomposition of Nd-Cu at 520°C [6,7]. Crystal structure changes of the Nd-rich phase, induced by PSA, have been also reported using a simple model system [8][9][10]. The most stable hNd 2 O 3 phase is formed away from the Nd 2 Fe 14 B//Nd-rich phase interface, but the meta-stable fcc-NdO 2 phase (a = 0.54 nm), which is related to the C-Nd 2 O 3 (Ia 3, a = 1.108 nm) phase, is formed at the interface in the sample whose coercivity was recovered during 550°C annealing [8][9][10].…”
Section: Introductionmentioning
confidence: 83%
“…Crystal structure changes of the Nd-rich phase, induced by PSA, have been also reported using a simple model system [8][9][10]. The most stable hNd 2 O 3 phase is formed away from the Nd 2 Fe 14 B//Nd-rich phase interface, but the meta-stable fcc-NdO 2 phase (a = 0.54 nm), which is related to the C-Nd 2 O 3 (Ia 3, a = 1.108 nm) phase, is formed at the interface in the sample whose coercivity was recovered during 550°C annealing [8][9][10]. This suggests that the meta-stable fccNdO 2 (or C-Nd 2 O 3 ) could be stabilized by the energy of the interface with the Nd 2 Fe 14 B phase [8][9][10].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…If the liquid phase after the high temperature annealing exists at the center of triple junctions, as described above, it is considered that the precipitated dhcp-Nd and hcp-Nd 2 O 3 from liquid phase do not contact with Nd 2 Fe 14 B main phases. Fukagawa and Hirosawa 18) have reported that dchp-Nd does not contribute to the recover of coercivity even after annealing. Therefore, it can be said that the roles of high temperature annealing are to precipitate the fcc-NdO from the liquid phase along the Nd 2 Fe 14 B grains and to move the residual liquid phase at the center of triple junctions.…”
Section: Resultsmentioning
confidence: 99%
“…The Nd-rich phases near the main phase are reported to be metastable oxide phases [9,10]. Many researchers have shown that the Nd-rich phase was essential to improve coercivity and thermal stability for sintered Nd-Fe-B magnets.…”
Section: Introductionmentioning
confidence: 98%